Gambaran Kesejahteraan Psikologis Lansia di Panti Wredha Merbabu Salib Putih Kota Salatiga: Description of the Psychological Well-being of the Elderly in Nursing Homes White Cross Merbabu, Salatiga City - Liyanovitasari; Umi Setyoningrum (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2025)
The elderly period is marked by various changes, both in physical, psychological, and social aspects, which directly affect their physical and mental conditions. Physical changes that occur in the elderly often have an impact on their psychological condition. Psychological well-being can increase if the elderly get good support from family, friends, and the surrounding environment. The psychological well-being of the elderly is good if the aspects of self-acceptance, positive relationships with others, autonomy, mastery of the environment, having a purpose in life that provides direction and meaning in life, and self-growth are fulfilled. The purpose of this study was to determine the description of psychological well-being in the elderly at the Nursing Home. Method: The design of this study is descriptive quantitative. The population in this study were 105 elderly elderly who lived at the Salib Putih Nursing Home of Salatiga, 83 samples were selected using a purposive sampling technique. The measuring instrument used was the Ryff's Psychological Well Being questionnaire for psychological well-being. The data analysis used was univariate analysis. Results: Most respondents are in the elderly category, 63 respondents (75.9%), the gender of the respondents is mostly female, 53 respondents (63.9%), the education of the respondents is mostly high school, 51 respondents (61.4%), the length of stay in the nursing home, most respondents are more than 1 year, 72 respondents (86.7%). Most of the elderly have moderate psychological well-being, 45 respondents (54.2%). Suggestion: In order for the psychological well-being of the elderly to be fulfilled, the elderly must improve positive relationships with others and be able to accept their shortcomings. ABSTRAK Masa lansia ditandai oleh berbagai perubahan, baik dalam aspek fisik, psikologis, maupun sosial, yang secara langsung memengaruhi kondisi tubuh dan mental mereka. Perubahan fisik yang terjadi pada lansia seringkali berdampak pada kondisi psikologis mereka. Kesejahteraan psikologis dapat meningkat apabila lansia mendapatkan dukungan baik dari keluarga, teman, dan lingkungan sekitarnya. Kesejahteraan psikologis lansia baik apabila terpenuhi aspek penerimaan diri, hubungan positif dengan orang lain, otonomi, penguasaan lingkungan, memiliki tujuan hidup yang memberikan arah dan makna dalam kehidupan, dan pertumbuhan diri. Tujuan penelitian ini adalah mengetahui gambaran kesejahteraan psikologis pada lansia di Panti Wredha. Desain penelitian ini yaitu deskriptif kuantitatif. Populasi dalam penelitian ini lansia yang bertempat tinggal di Panti Wredha Merbabu Salib Putih Salatiga sejumlah 105 lansia, dipilih sejumlah 83 sampel dengan teknik purposive sampling. Alat ukur yang digunakan adalah kuesioner Ryff’s Psychological Well Being untuk kesejahteraan psikologis. Analisis data yang digunakan yaitu analisis univariat. Hasil : Sebagian besar responden memiliki usia kategori lanjut usia tua sebanyak 63 responden (75,9%), jenis kelamin responden sebagian besar perempuan sebanyak 53 responden (63,9%), pendidikan responden sebagian besar SMA sejumlah 51 responden (61.4%), lama tinggal di panti sebagian besar responden lebih dari 1 tahun sebanyak 72 responden (86.7%). Lansia sebagian besar memiliki kesejahteraan psikologis kategori sedang sebanyak 45 responden (54.2%). Lansia memiliki kategori kesejahteraan psikologis sedang. Kesejahteraan psikologis lansia agar terpenuhi maka lansia harus meningkatkan hubungan positif dengan orang lain, dan dapat menerima kekurangan dirinya.